2022
DOI: 10.3724/abbs.2022176
|View full text |Cite
|
Sign up to set email alerts
|

The pseudogene DUXAP10 contributes to gefitinib resistance in NSCLC by repressing OAS2 expression

Abstract: Gefitinib, an epidermal growth factor receptor-tyrosine kinase inhibitor (EGFR-TKI),is the currently recommended first-line therapy for advanced EGFR-mutant lung cancer, and understanding the mechanism of resistance is the key to formulating therapeutic strategies for EGFR-TKIs. In this study, we evaluate the expression patterns and potential biological functions of the pseudogene DUXAP10 in gefitinib resistance. We find that pseudogene DUXAP10 expression is significantly upregulated in NSCLC gefitinib-resista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Further research in colorectal cancer has con rmed that OAS2 upregulates the expressions of E-cadherin, β-catenin, claudin-1 and snail, which induces autophagy and prolongs recurrence-free survival (RFS)(8). A recent study indicates that OAS2 plays a role in ge tinib resistance as a tumor suppressor (20). While in another study, downregulation of OAS2 promotes the sensitivity of acute myeloid leukemia cells to chemotherapy drugs (21).…”
Section: Introductionmentioning
confidence: 95%
“…Further research in colorectal cancer has con rmed that OAS2 upregulates the expressions of E-cadherin, β-catenin, claudin-1 and snail, which induces autophagy and prolongs recurrence-free survival (RFS)(8). A recent study indicates that OAS2 plays a role in ge tinib resistance as a tumor suppressor (20). While in another study, downregulation of OAS2 promotes the sensitivity of acute myeloid leukemia cells to chemotherapy drugs (21).…”
Section: Introductionmentioning
confidence: 95%
“…In addition, although CT is noninvasive and highly sensitive, it is often accompanied by overdiagnosis [ 2 , 3 ]. Several studies have confirmed the effects of noncoding RNAs (ncRNAs) and mRNAs on the early screening and biological progression of NSCLC, such as the inhibition of growth, ING5 overexpression, miR-34c-5p/Snail1 inhibition of EMT and lung cancer cell invasion [4] , and on the pseudogene DUXAP10 which contributes to gefitinib resistance in NSCLC by inhibiting OAS2 expression [5] . Therefore, the screening of simple and efficient diagnostic markers and the development of minimally invasive techniques for the diagnosis of early-stage NSCLC are of great clinical importance.…”
Section: Introductionmentioning
confidence: 99%